STUDI KASUS DAMPAK OVERTHINKING DALAM PERENCANAAN KARIR MASA DEPAN PADA SISWA KELAS VIII B SMP NEGERI 18 SURAKARTA TAHUN AJARAN 2025/2026 - Laila Jeni Ramanda; Suryanti, Hera Heru Sri; Jawandi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Laila Jeni Ramanda, CASE STUDY OF THE IMPACT OF OVERTHINKING IN FUTURE CAREER PLANNING OF GRADE VIII B STUDENTS OF SMPN 18 CITY OF SURAKARTA IN THE ACADEMIC YEAR 2025/2026. Surakarta: Faculty of Teacher Training and Education, Slamet Riyadi University, Surakarta. March 2026. The purpose of this research is to determine the impact of overthinking that can influence the future career planning process in Grade VIII B students of SMPN 18 Surakarta in the Academic Year 2025/2026.This research was conducted at SMPN 18 Surakarta. This research form used a qualitative method. This research strategy employed a case study strategy The subjects in this study Included the Guidance and Counseling Teacher, students who faced overthinking, and parents. The data sources used were primary data sources and secondary data sources. The data collection techniques used were interviews, observation, and documentation. Data validity was tested using source trangulation and technique triangulation. The results of this study could be concluded that the phenomenon of overthinking has a significant impact that hinders the effectiveness of students' career planning through the manifestation of analysis paralysis behavior and negative rumination. Research findings indicated that students with ambitious tendencies often engaged in excessive long-term risk processing in pursuit of perfect outcomes, thereby hindering quick and accurate decision-making processes. On the other hand, students with low self-confidence showed a defensive and pessimistic attitude, where they tended to imagine failure scenarios before trying, which ultimately paralyzed their motivation to explore their interests and talents objectively.